2004
DOI: 10.1097/01.tp.0000128613.74683.d9
|View full text |Cite
|
Sign up to set email alerts
|

Delta Analysis of Posttransplantation Tubulointerstitial Damage

Abstract: CIF was a result of early ischemia-reperfusion injury, acute, subacute or persistent interstitial inflammation occurring in a time-dependent manner and was considerably modified by immunosuppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 25 publications
9
86
1
2
Order By: Relevance
“…These data confirmed the findings described by Nankivell et al (13) in which interstitial fibrosis showed an adverse impact on graft outcome (13)(14)(15)(16)(17). Furthermore, interstitial fibrosis is a common finding in other chronic kidney diseases besides chronic allograft nephropathy (13), having strong correlation with tubular atrophy and graft loss (13,18).…”
Section: Discussionsupporting
confidence: 82%
“…These data confirmed the findings described by Nankivell et al (13) in which interstitial fibrosis showed an adverse impact on graft outcome (13)(14)(15)(16)(17). Furthermore, interstitial fibrosis is a common finding in other chronic kidney diseases besides chronic allograft nephropathy (13), having strong correlation with tubular atrophy and graft loss (13,18).…”
Section: Discussionsupporting
confidence: 82%
“…These increases in cv, ah, ci and ct correlated strongly with decreased cGFR at 36 months. This suggests that reduced tubulointerstitial and vascular damage seen in patients treated with belatacept is related to the better allograft function seen through 36 months (3,26,27), although multiple factors may contribute to CAI.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, biopsies obtained from renal transplant recipients at day 0 and month 3 and 12 showed a rapid progression of IF scores from 19% to 27% at month 3 and 32% at month 12 (363). Other studies have also found that progression of IF is particularly prominent early after transplantation (365), suggesting that this is a window for therapeutic intervention. Additional analyses might further improve the predictive value of allograft biopsies such as the immunohistochemical detection of CD44 and vimentin (366), activation markers of parietal epithelial cells as markers of FSGS in the renal transplant (367), or immunohistochemistry aided analyses of peritubular capillaries to detect their early and progressive rarefaction in allografts (368).…”
Section: Diagnosis Of Renal Fibrosismentioning
confidence: 87%